Let's Write it Down, No Let's Be Friends First. - Dennis Day (Journal of Modern Languages)
This paper presents a qualitative case study of communicative interaction between a Malay-Malaysian (MM) and a Chinese-Malaysian (CM). The study investigates the notions of rules of speaking in relation to how these two individuals, with quite different sociocultural backgrounds, work towards the goals of a specific social activity, planning a short presentation entitled ‘Malaysia: people, progress, and problems’.